The Utility of activated Partial Thromboplastin Time (aPTT) Clot Waveform Analysis in the Investigation of Hemophilia A Patients with very Low Levels of Factor VIII Activity (FVIII:C) - Shima, Midori; Matsumoto, Tomoko; Fukuda, Kazuyoshi; Kubota, Youko; Tanaka, Ichiro; Nishiya, Katumi; Giles, Alan R.; Yoshioka, Akira (Thrombosis and Haemostasis, 2002)
The lower detection limit of the conventional one-stage aPTT based clotting assay for determining FVIII:C levels is generally 1.0-2.0 IU/dl. Consequently, it has been impossible to study the clinical significance of levels of FVIII:C less than 1.0 IU/dl. Using a photo-optical automated coagulation analyzer, the Organon Teknika MDA II®, we have performed qualitative and quantitative aPTT waveform analysis and measured FVIII:C levels by automated one-stage aPTT clotting assay in 36 severely affected Hemophilia A patients. Qualitative waveform analysis showed clear evidence of individual differences in the waveform profile suggesting differing coagulant activity from patient to patient. The FVIII:C level was less than 0.2 IU/dl in 23 cases and levels of FVIII:C between 0.2 and 1.0 IU/dl could be discriminated in 13 patients. The FVIII:C level in these patients was closely correlated with the minimum value of the second derivative of the aPTT waveform (Min2). This is a measure of the acceleration of change in optical transmission at the initiation of coagulation. Furthermore, the correlation of the aPTT (time and Min2) and the FVIII:C level, determined by a one-stage clotting assay on the same system, was high in plasmas with a range of levels of FVIII:C artificially prepared by the addition of various concentrations of rFVIII:C to FVIII deficient plasma. These data suggest that it is possible to segregate different levels of clotting activity in patients previously assigned to a single grouping, i.e. less than 1.0 IU/dl, by conventional one-stage assay. Thus clot waveform analysis may be useful for the investigation of the clinical phenotype of individual patients and their response to therapy.
Keywords: Factor VIII (FVIII); factor VIII activity (FVIII:C); waveform analysis